1995
DOI: 10.1111/j.1476-5381.1995.tb15036.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of P2‐purinoceptor antagonists on glutamatergic transmission in the rat hippocampus

Abstract: 1 A study has been made of the effects of P2-purinoceptor antagonists on the evoked excitatory postsynaptic currents (e.p.s.cs) generated in CAl pyramidal cells on stimulation of Schaffer collaterals and in CA3 pyramidal cells on stimulation of mossy fibres. The effects of these antagonists on currents generated in the cells on application of glutamate has also been determined. 2 Suramin blocked the evoked e.p.s.cs with an 50% inhibition (ID50) of 62 ± 8 Mm (mean±s.e.mean, n = 17), spontaneous miniature e.p.s.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
33
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 37 publications
5
33
0
Order By: Relevance
“…Furthermore, it should be emphasized that in contrast to the P2 receptor antagonists suramin and reactive blue 2 no direct glutamate antagonistic properties were found for PPADS (Fröhlich et al, 1996;Motin and Bennett 1995;Gu et al, 1998). The anxiolytic-like effects of ADPbS were also abolished after pretreatment with MRS 2179, which acts as a specific P2Y 1 receptor antagonist (Boyer et al, 1998).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, it should be emphasized that in contrast to the P2 receptor antagonists suramin and reactive blue 2 no direct glutamate antagonistic properties were found for PPADS (Fröhlich et al, 1996;Motin and Bennett 1995;Gu et al, 1998). The anxiolytic-like effects of ADPbS were also abolished after pretreatment with MRS 2179, which acts as a specific P2Y 1 receptor antagonist (Boyer et al, 1998).…”
Section: Discussionmentioning
confidence: 96%
“…P 2 receptor-mediated excitation has only been demonstrated for inspiratory-modulated hypoglossal motoneurons in neonatal mouse (in vitro), and adult rat (in vivo) (403) With the consideration that ATP acts as the principal fast excitatory transmitter at some central synapses (320,345), ATP may directly mediate specific behavioral inputs. Alternatively, ATP may modulate glutamatergic synaptic transmission (736,872) to motoneurons (403). P 2y receptors are present in the CNS (61); however, their role in motor control remains to be established.…”
Section: H Achmentioning
confidence: 99%
“…There are also reports that suramin inhibits glutamatergic synaptic transmission (Motin and Bennett, 1995;Gu et al, 1998) and whole-cell currents mediated by AMPA receptors (Nakazawa et al, 1995;Zona et al, 2000) and NMDA receptors (Ong et al, 1997;Peoples and Li, 1998). Suramin was observed to inhibit binding of radioligands to NMDA receptors (Balcar et al, 1995) but not kainate receptors (Ong et al, 1997), which suggested some selectivity among glutamate receptors.…”
mentioning
confidence: 99%
“…A somewhat distinct structural family of purinoceptor antagonists was established some time ago with the development of PPADS (Lambrecht et al, 1992), which has since been widely used as a highly selective P2X receptor blocker. This compound does not have mirror symmetry, is much smaller than suramin, and was indeed found to have no or weak effects on glutamate receptor responses (Motin and Bennett, 1995;Gu et al, 1998;Zona et al, 2000). PPNDS, another member of this drug family, has recently been identified as having even greater affinity for P2X receptors and a marked selectivity toward the P2X1 receptor subtype with a nanomolar inhibition constant .…”
mentioning
confidence: 99%